PANDANGAN CITRA BRAND KOPI JANJI JIWA DI KALANGAN MAHASISWA - Rayni Delya Hafni (Jurnal Ilmiah Komunikasi Makna, 2020)
Increased coffee consumption continues to occur in Indonesian society, even Indonesia is referred to as the country with the highest level of consumption in the world. Coffee is not only enjoyed by several groups, but coffee can be enjoyed by all circles across generations and genders. Janji Jiwa is one of the coffee shops or brands in Indonesia. This shop has been opened since 2018 and is enough to attract public attention. Currently Janji Jiwa continues to develop its brands and coffee products to be better and be able to compete with supporters One of the concepts that are featured in the Janji Jiwa brand is the fresh-to-cup concept of using coffee from local Indonesian farmers. The purpose of this study is to study the public's view of the Kopi Janji Soul brand image and strategies that can be used to improve brand image among students today. This study uses qualitative methods with data collection techniques using in-depth interviews. The population in this study were students. From the research results, it shows that: (1) The quality of services provided by students, (2) Unique brand names are a special attraction for some people, (3) Strong marketing strategies and psychological influence, (4) social and psychological factors , (5) Differences of opinion regarding the taste of coffee. From the results of this research, Janji Jiwa can continue to use its marketing strategy but this brand must also continue to innovate in coffee products so that the product can also be promoted by all groups and enhance a positive brand image.